2021
DOI: 10.3390/buildings11110504
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Social Impacts of High-Rise Residential Buildings during the Post-Occupancy Phase Using DEMATEL Method: A Case Study

Abstract: There are numerous risks associated with high-rise buildings, which not only affect stakeholders during the design and construction phase but also impact the occupants and the surrounding environment during the post-occupancy phase. While previous studies examined the risks of high-rise building construction, less attention has been paid to the diverse impacts of high-rise buildings on their occupants. To fill this gap, this study applied a mixed-method approach (both quantitative and qualitative) to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Considering there are a total number of 15 dispute causes extracted in this study, only the top three causes from different perspectives were selected to represent the decisive causes. This approach is consistent with other similar studies [44,59,60].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Considering there are a total number of 15 dispute causes extracted in this study, only the top three causes from different perspectives were selected to represent the decisive causes. This approach is consistent with other similar studies [44,59,60].…”
Section: Discussionsupporting
confidence: 93%
“…Costa et al [43] used the DEMATEL technique to provide a new understanding of the barriers to improve the customer-supplier relationship in construc-tion supply chains by showing cause-effect relationships among these barriers. Dwijendra et al [44] identified the most important and influential social impacts of high-rise buildings during the post-occupancy phase using the DEMATEL method.…”
Section: Use Of Dematel Methodologymentioning
confidence: 99%
“…Eqs. ( 14)-( 16) are discounting factor for replacement, discounting factor operation and maintenance and salvage cost of the resources at project lifetime, respectively [36]- [40]. And modelling OC is given by ( 17):…”
Section: Modelling Objective Functionsmentioning
confidence: 99%
“…Countries with high income inequality usually have a relatively poor level of political and economic institutes. Even if the institutional structure of such a country is good enough, it may not work as well as in democratic regimes (Zhuang et al 2010;Kosov et al 2018;Kosov et al 2019;Sulemana and Kpienbaareh 2018;Dwijendra et al 2021). Furthermore, an excessive level of income inequality can degrade the institutional structure of an economy, even in democratic countries and slow down economic growth (Policardo and Carrera 2004;Kotschy and Sunde 2004;Batabyal and Chowdhury 2015;Berisha et al 2018).…”
Section: The Review Of Empirical Studies On the Impact Of Economic In...mentioning
confidence: 99%